2023
DOI: 10.1038/s41398-023-02321-9
|View full text |Cite
|
Sign up to set email alerts
|

Latent class analysis of psychotic-affective disorders with data-driven plasma proteomics

Abstract: Data-driven approaches to subtype transdiagnostic samples are important for understanding heterogeneity within disorders and overlap between disorders. Thus, this study was conducted to determine whether plasma proteomics-based clustering could subtype patients with transdiagnostic psychotic-affective disorder diagnoses. The study population included 504 patients with schizophrenia, bipolar disorder, and major depressive disorder and 160 healthy controls, aged 19 to 65 years. Multiple reaction monitoring was p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…Proteomics analysis is a powerful approach to mitigate conundrums of diseases in clinical research, which has been demonstrated in previous studies. Particularly, targeted proteomics using multiple reaction monitoring-mass spectrometry (MRM-MS) is regarded as a powerful quantitative method that is advantageous compared with antibody-based assays in terms of multiplex ability, high throughput, and reproducibility. Recently, we have been constructing diagnostic multiprotein models for various diseases using MRM-MS and machine learning (ML) methods. When it comes to discrimination of psychiatric disorders, we previously developed models to distinguish between MDD, BD, and SCZ with high accuracy using MRM-MS in depleted plasma samples. , Although the constructed models had high distinguishability, the depletion process of high abundant proteins is time-consuming and labor-intensive, which takes around half of the total time of sample preparation. In this study, we improved our LC-MRM-MS method to detect and quantify as many proteins as possible with nondepleted plasma in a single MRM-MS assay. Next, we aimed to demonstrate the potential of nondepleted plasma multiprotein-based models to discriminate psychiatric disorders using ML approaches, and to compare these with our previous models .…”
Section: Introductionmentioning
confidence: 99%
“…Proteomics analysis is a powerful approach to mitigate conundrums of diseases in clinical research, which has been demonstrated in previous studies. Particularly, targeted proteomics using multiple reaction monitoring-mass spectrometry (MRM-MS) is regarded as a powerful quantitative method that is advantageous compared with antibody-based assays in terms of multiplex ability, high throughput, and reproducibility. Recently, we have been constructing diagnostic multiprotein models for various diseases using MRM-MS and machine learning (ML) methods. When it comes to discrimination of psychiatric disorders, we previously developed models to distinguish between MDD, BD, and SCZ with high accuracy using MRM-MS in depleted plasma samples. , Although the constructed models had high distinguishability, the depletion process of high abundant proteins is time-consuming and labor-intensive, which takes around half of the total time of sample preparation. In this study, we improved our LC-MRM-MS method to detect and quantify as many proteins as possible with nondepleted plasma in a single MRM-MS assay. Next, we aimed to demonstrate the potential of nondepleted plasma multiprotein-based models to discriminate psychiatric disorders using ML approaches, and to compare these with our previous models .…”
Section: Introductionmentioning
confidence: 99%
“…For clinical practice, studies of biological fluids are more popular, according to which various physiological states of organs and systems, including the brain, are reflected in their composition [32,33]. Therefore, it is important to study potential biomarkers of mental disorders in an easily accessible material-blood serum [34][35][36][37][38][39][40][41]. However, all discovered proteins do not solve the problem of differential diagnosis of mental disorders due to their non-specificity.…”
Section: Introductionmentioning
confidence: 99%